2013
DOI: 10.1371/journal.pntd.0002437
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Infections of Giardia duodenalis, Enterocytozoon bieneusi, and Clostridium difficile in Children during a Cryptosporidiosis Outbreak in a Pediatric Hospital in China

Abstract: BackgroundOver 200 cryptosporidiosis outbreaks have been reported, but little is known if other enteric pathogens were also involved in some of these outbreaks. Recently, an outbreak of cryptosporidiosis linked to poor hygiene by two Cryptosporidium hominis subtypes occurred in a pediatric hospital ward (Ward A) in China, lasting for more than 14 months. In this study, the concurrence during the outbreak of three other enteric pathogens with a similar transmission route, Giardia duodenalis, Enterocytozoon bien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
154
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(167 citation statements)
references
References 29 publications
11
154
2
Order By: Relevance
“…The extent of genetic relationships among E. bieneusi genotypes identified in this study was evaluated by molecular phylogenetic analysis using the neighbor-joining method, which showed clustering of the known genotypes CS-4 (subgroup 1e), EbpC (1d), Henan-IV (1d), and the new genotypes NEC1 (1d), NEC2 (1d), NEC3 (1e), NEC4 (1d), and NEC5 (1e) in genetic group 1 with the zoonotic potential described by Thellier and Breton (4) (8), genotypes D, EbpA, EbpC, Henan-I (reported as SH7), IV (reported as SH12), Peru11, SH1 to SH4, SH6, and SH8 to SH11 in children in the city of Shanghai in central China (9), and some other genotypes previously reported in humans and pigs in other geographic areas of the world (3). Zoonotic potential and public health significance.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The extent of genetic relationships among E. bieneusi genotypes identified in this study was evaluated by molecular phylogenetic analysis using the neighbor-joining method, which showed clustering of the known genotypes CS-4 (subgroup 1e), EbpC (1d), Henan-IV (1d), and the new genotypes NEC1 (1d), NEC2 (1d), NEC3 (1e), NEC4 (1d), and NEC5 (1e) in genetic group 1 with the zoonotic potential described by Thellier and Breton (4) (8), genotypes D, EbpA, EbpC, Henan-I (reported as SH7), IV (reported as SH12), Peru11, SH1 to SH4, SH6, and SH8 to SH11 in children in the city of Shanghai in central China (9), and some other genotypes previously reported in humans and pigs in other geographic areas of the world (3). Zoonotic potential and public health significance.…”
mentioning
confidence: 97%
“…Genotypic typing and phylogenetic analysis facilitated classification of the almost 200 genotypes identified thus far into genetic group 1 with zoonotic potential and several other host-adapted genetic clusters (4)(5)(6)(7). Infections with E. bieneusi in humans have been repeatedly reported worldwide, although epidemiologic data to indicate the prevalence and risk of human microsporidiosis in China are limited (8)(9)(10). The frequent and close contact of humans with livestock in China is of potential zoonotic concern (6,7).…”
mentioning
confidence: 99%
“…Foodborne disease outbreaks linked to multiple pathogens could be common yet are rarely reported (Berkelman et al, 1983;Naimi et al, 2003;Wang et al, 2013). In this case, multiple pathogens were detected in the specimens from the outbreak.…”
Section: Discussionmentioning
confidence: 79%
“…BEB6 was the most frequently found genotype, accounting for 28% (13/46) of all positive samples. To date, BEB6 has been usually derived from animals (especially sheep and cattle) (Ye et al 2015, Zhao et al 2015, but also identified in human and nonhuman primates in Henan Province (Wang et al 2013, Karim et al 2014b. Genotypes I and J reported in captive wildlife in Zhengzhou had also been detected in humans in Jilin, China (Zhang et al 2011).…”
Section: Discussionmentioning
confidence: 99%